Synthesis of high quality two-dimensional materials via chemical vapor deposition. Issue 12 (19th August 2015) - Yu, Jingxue; Li, Jie; Zhang, Wenfeng; Chang, Haixin
Abstract : The synthesis of high quality two-dimensional materials such as graphene, BN, and transition metal dichalcogenides by CVD provides a new opportunity for large scale applications. Abstract : Two-dimensional (2D) materials have attracted much attention due to their unique properties and great potential in various applications. Controllable synthesis of 2D materials with high quality and high efficiency is essential for their large scale applications. Chemical vapor deposition (CVD) has been one of the most important and reliable techniques for the synthesis of 2D materials. In this perspective, the recent advances in the CVD growth of three typical types of two-dimensional materials, graphene, boron nitride and transition metal dichalcogenides (TMDs), are briefly introduced. Large area preparation, single crystal growth and some mechanistic insight are discussed with details. Finally we give a brief comment on the challenges of CVD growth of 2D materials.